Association between objective measurement of the speech intelligibility of young people with dysarthria and listener ratings of ease of understanding. (August 2014) - Landa, Sophie; Pennington, Lindsay; Miller, Nick; Robson, Sheila; Thompson, Vicki; Steen, Nick
Abstract Purpose: This study aimed to investigate the association between listeners' ratings of how much effort it took to understand the speech of young people with cerebral palsy and the percentage of words listeners actually understood. Method: Thirty-one young people with dysarthria and cerebral palsy (16 males, 15 females; mean age = 11 years, SD = 3) were audio recorded repeating single words and producing speech. Objective measures of intelligibility were calculated for multiple familiar and unfamiliar listeners using a forced choice paradigm for single words and verbatim orthographic transcriptions for connected speech. Listeners rated how much effort it took to understand speech in each condition using a 5-point ordinal ease of listening (EOL) scale. Results: Agreement on EOL within rater groups was high (ICC > 0.71). An effect of listener was observed for familiar listeners, but not for unfamiliar listeners. EOL agreement between familiar and unfamiliar listeners was weak–moderate (ICC = 0.46). EOL predicted the percentage of speech actually understood by familiar and unfamiliar listeners (r > 0.56, p < 0.001 for all predictions). Strongest associations between EOL and intelligibility were observed for speakers with mild and profound impairments. Conclusions: The findings of this study demonstrate that listeners can judge how well they have understood dysarthric speech. EOL is associated with listener familiarity, speech task and speech impairment severity. EOL is appropriate for use in clinical practice as a measure of communication activity.